Enhancing Thermoelectric Performance of TiNiSn Half-Heusler Compounds via Modulation Doping - Berry, Tanya; Fu, Chenguang; Auffermann, Gudrun; Fecher, Gerhard H.; Schnelle, Walter; Serrano-Sanchez, Federico; Yue, Yuan; Liang, Hong; Felser, Claudia (Chemistry of Materials, 2017)
MNiSn (M = Ti, Zr, and Hf) half-Heusler (HH) compounds are widely studied n-type thermoelectric (TE) materials for power generation. Most studies focus on Zr- and Hf-based compounds due to their high thermoelectric performance. However, these kinds of compositions are not cost-effective. Herein, the least expensive alloy in this half-Heusler family - TiNiSn - is investigated. Modulation doping of half-metallic MnNiSb in the TiNiSn system is realized by using spark plasma sintering. It is found that MnNiSb dissolves into the TiNiSn matrix and forms a heavily doped Ti1-xMnxNiSn1-xSbx phase, which leads to largely enhanced carrier concentration and also slight increase of carrier mobility. As a result, the electrical conductivity and power factor of the modulation doped compounds are greatly improved. A maximum power factor of 45 × 10-4 W K-2 m-1 is obtained at 750 K for the modulation doping system (TiNiSn)1-x + (MnNiSb)x with x = 0.05, which is one of the highest reported values in literature for TiNiSn systems. Furthermore, the lattice thermal conductivity is also suppressed due to the enhanced phonon scattering. Beneficial from the improved power factor and suppressed lattice thermal conductivity, a peak zT of 0.63 is obtained at 823 K for x = 0.05, which is an ∼70% increase compared to the peak zT of TiNiSn. These results highlight the potential application of inexpensive TiNiSn-based TE materials and the effectiveness of modulation doping in enhancing the TE performance of HH compounds.
CRIS-Team Scopus Importer:2022-04-14